PENANGANAN KESULITAN BELAJAR SISWA MELALUI LAYANAN BIMBINGAN KELMPOK DI SMP NEGRI 3 KARAWANG BARAT - Zahra Ismaya, Siti; Febri Dahlia , Febri Dahlia; Feny Nida Fitriyani , Feny (IKIP Siliwangi, 2025)
Learning difficulties are one of the problems often faced by students, especially during early adolescent development such as grade VIII of junior high school. This study aims to analyze the effectiveness of group guidance in helping students overcome learning difficulties. The method used in this study is descriptive qualitative on grade VIII students of SMP 3 Karawang Barat. Data processing through observation, interviews, and documentation related to the research object. Data analysis techniques were carried out interactively for two months. The results of observations and interviews showed that students' learning difficulties were divided into two categories, namely cognitive difficulties and academic difficulties. Group guidance services were designed and implemented to help overcome these problems. The results showed that before participating in group guidance, students showed symptoms such as low motivation, inability to understand the material, and low self-confidence. After participating in four sessions of group guidance based on a humanistic approach, students experienced a significant increase in learning participation, understanding of the material, and academic motivation. These findings indicate that group guidance can be an effective strategy in overcoming learning difficulties in grade VIII students holistically through a collaborative and reflective approach.